URGENSI SOSIOLOGI SEBAGAI BAGIAN DALAM DIMENSI STUDI ISLAM - Ulum, Miftahul; Ghani, Abd; Mohsi, Mohsi (Ulumuna: Jurnal Studi Keilsman, 2022)
This study focuses on Islamic studies with a sociological approach. Islamic studies require an approach that is able to provide grounded answers, sociological studies are one that researchers can do. The social problems faced by society are the manifestation of human thought patterns and understanding of religion. Sociology is a science that studies the interaction between individuals as a manifestation of the nature of living together, so that religion has a role in maintaining harmony in social life. This study uses a literature review approach by making sociological figures as part of the primary source. The results of the study show that the dominance of this sociological approach in responding to society and society is proof that this approach is very easy to understand religion and preserve the sharia elements of that religion. The influence of social life on the development of religion can be proven by social approaches. At the same time, religion can also influence people in their actions. Thus, the existence of religion is a solution for any social phenomena that are and will occur, without eliminating the existence of religion which is sacred and dynamic.Keyword: Sociology, Dimension, Islamic Studies